PERAN GURU BACA TULIS AL-QUR'AN DALAM MENINGKATKAN KEMAMPUAN MEMBACA AL-QUR'AN DI KELAS IV B SDS IT SULTHONIYAH SAMBAS TAHUN AJARAN 2025/2026 - Dwi Lieviani; Asyruni Multahada; Effiyadi (CV. ADIBA ASIHA AMIRA, 2026)
This study was motivated by the varying levels of students' ability to read the Qur'an, particularly among the fourth-grade students of Class IV B at SDS IT Sulthoniyah Sambas. While some students are able to read the Qur'an fluently, others still experience difficulties in recognizing the hijaiyah letters, applying proper makhraj (pronunciation), and mastering the rules of tajwid. Therefore, the role of the Qur'an Reading and Writing (BTQ) teacher is considered crucial in improving students' Qur'an reading ability. This study aims to: (1) describe the role of the BTQ teacher in improving students' Qur'an reading ability; (2) identify the teaching methods and strategies employed in BTQ learning; and (3) determine the supporting and inhibiting factors encountered during the learning process. This research employed a qualitative approach with a descriptive research design. Data were collected through observation, interviews, and documentation. The research subjects were the students of Class IV B, while the informants consisted of the BTQ teacher, the classroom teacher, and the school principal. Data were analyzed through data reduction, data display, and conclusion drawing, while the validity of the data was ensured through triangulation. The findings reveal that the BTQ teacher plays a significant role as an educator, instructor, mentor, motivator, facilitator, and evaluator in enhancing students' Qur'an reading ability. The teaching methods and strategies applied include the talaqqi approach, the sorogan method, classical learning, drill (repetitive practice), and the habituation of Qur'an reading. Supporting factors include students' learning motivation, teacher competence, the use of varied teaching methods, and support from the school environment. Meanwhile, the inhibiting factors include differences in students' abilities, low learning motivation, limited instructional time, and insufficient parental support. It can therefore be concluded that the role of the BTQ teacher has a significant influence on improving students' Qur'an reading ability. Consequently, appropriate instructional strategies and support from various stakeholders are essential to achieve optimal learning outcomes.